Solution of 2nd Order Nonlinear Three-Point Boundary Value Problems By Semi-Analytic Technique - Tawfiq, Luma N. M.; Hilal, Mariam M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we present new algorithm for the solution of the second order nonlinear three-point boundary value problem with suitable multi boundary conditions. The algorithm is based on the semi-analytic technique and the solutions which are calculated in the form of a rapid convergent series. It is observed that the method gives more realistic series solution that converges very rapidly in physical problems. Illustrative examples are provided to demonstrate the efficiency and simplicity of the proposed method in solving this type of three point boundary value problems.